Application of Ontology Using the Protégé Editor: An Applied Study in Semantic Knowledge Organization and Representation (The International Journal for Scientific Research, 2026)
This study aims to analyze the role of the Protégé program as a supportive tool for organizing and representing semantic knowledge within the framework of information science and knowledge management, in light of the limited number of Arabic studies that have examined it from the perspective of knowledge organization and linked its technical features to knowledge management processes. The study adopts a documentary approach through a review of the relevant scientific literature on ontologies, the Semantic Web, and ontology development tools. In addition, the content analysis method is employed in the applied component to analyze the outputs of using Protégé, through the construction of a simplified ontological model using Protégé (version 5.6.7).The applied component focuses on testing the extent to which a set of criteria derived from systems engineering literature, as proposed by Uschold and Gruninger (1996), namely specification, reliability, and reusability, can be applied to the outputs of the program, with the aim of evaluating its effectiveness in organizing and representing knowledge. The findings indicate that ontology constitutes a central tool for organizing and representing knowledge within intelligent environments, and that Protégé provides a flexible and structured environment for ontology development. It also supports the representation of semantic relationships between concepts through tools for class creation, property and relationship definition, and the use of logical reasoning engines to verify consistency.In light of these findings, the study concludes that Protégé represents a robust application environment for enhancing the practical dimension of ontology in the context of knowledge organization and representation. It further emphasizes the importance of employing Protégé within an integrated framework alongside other knowledge management tools and technologies, while paying attention to linguistic and technical limitations when applying it in diverse organizational and institutional contexts.
Keywords: Knowledge Management; Knowledge Organization; Ontology; Protégé; Semantic Web; Semantic Representation; Knowledge Management Systems